Selection of Specialty and its satisfaction in Medical graduates - Tasleem, Huma; Akhter, Tasneem; Tasleem, Samina; Ghazanfar, Haider; Shamsunisa, Sadia (Bangladesh Journal of Medical Science, 2016)
Background: Selection of specialty in medical graduates is a challenging job. Consultants and residents are suffering from some unknown discomfort. The aim of this study was to survey the residents selection and their wish to change it and analyze the factors responsible for this wish. Methods: Cross sectional survey was done on residents of different specialty working in different hospitals of Rawalpindi and Islamabad (Pakistan) with the help of self-made questionnaire from 2012 to 2014. SPSS 21 was used to analyze the result. Results: We gave a total of 1200 questionnaires out of which 946 questionnaires were completely filled. Out of 946 residents, 48.5% (459) were male residents whereas 51.5% (487) were female residents. Majority of residents 75.4% (713) did not want to change their specialty whereas 24.6% (233) wanted to change their specialty if they would have been provided with such opportunity. Patient Contact, Interesting Diseases and Hospital based careers were the 3 main reasons for selecting a particular specialty. Night duties, Clinical Work and heavy work load were the 3 main causes for having the desire to leave their current specialty. Conclusion: Awareness should be given to medical students during their MBBS program about the challenges they would face in different specialty. Proper sessions should be arranged to help students realize their actual interest and identify field which would suit their temperament. Bangladesh Journal of Medical Science Vol.15(3) 2016 p.385-391